2016
DOI: 10.14336/ad.2015.1025
|View full text |Cite
|
Sign up to set email alerts
|

Levels and Rates of Physical Activity in Older Adults with Multiple Sclerosis

Abstract: There is much evidence supporting the safety and benefits of physical activity in adults with multiple sclerosis (MS) and recent evidence of beneficial effects on physical function in older adults with MS. However, there is very little known about physical activity participation in older adults with conditions such as MS. This study compared levels of physical activity (i.e., sedentary behavior, light physical activity (LPA), and moderate-to-vigorous physical activity (MVPA)) and rates of meeting public health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 30 publications
1
28
0
4
Order By: Relevance
“…Those with mobility disability demonstrated a greater number of bouts in sedentary behavior lasting for more than 30 min compared with those without mobility disability (5.1 vs. 4.3 bouts, p = 0.02). Another study using the ActiGraph 7164 accelerometer indicated that older adults with MS spent considerably more time in sedentary behavior than middle-aged and young adults with MS (554.1 vs. 532.8 vs. 509.6 min/day, respectively; p < 0.01) [57]. These data are important for characterizing sedentary behavior in MS and for allowing comparisons with the general population.…”
Section: Research From 2013–2017: What Is New?mentioning
confidence: 99%
“…Those with mobility disability demonstrated a greater number of bouts in sedentary behavior lasting for more than 30 min compared with those without mobility disability (5.1 vs. 4.3 bouts, p = 0.02). Another study using the ActiGraph 7164 accelerometer indicated that older adults with MS spent considerably more time in sedentary behavior than middle-aged and young adults with MS (554.1 vs. 532.8 vs. 509.6 min/day, respectively; p < 0.01) [57]. These data are important for characterizing sedentary behavior in MS and for allowing comparisons with the general population.…”
Section: Research From 2013–2017: What Is New?mentioning
confidence: 99%
“…First, our sample comprised majorly of middle‐aged (40‐59 years) and older adults aged ≥60 years. Given the literature suggesting that middle‐aged and older adults with MS are less physically active than young adults affected by the disease, it is possible that our findings may have been influenced by age‐related factors in addition to MS‐disability. Future researchers may want to explore the differences in PA perspectives between young and older adults affected by moderate‐to‐severe MS‐related disability.…”
Section: Discussionmentioning
confidence: 99%
“…and is rated on a 5-point Likert scale from 0 (Not at all confident) to 4 (Very confident). The items provide two sub-scores "Goal setting" (item 2, 3,4,5,6,7,8,13,14) and "Symptom management" (item 1,9,10,11,12,15). According to the authors [37], the scale is characterized by good item functioning, measurement invariance, and good concurrent validity (positive correlations with positive affect, sense of coherence and coping strategies and negative correlations with depression and negative affect).…”
Section: Methodsmentioning
confidence: 99%
“…However, people with MS do less PA compared to non-diseased people [7][8][9], but in similar way as other people suffering from a chronic disease [7]. Thus, according to different studies, people with MS are not getting the minimal amount of daily activity that even sedentary adults without neurologic injury or disease are able to achieve [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%